2022
DOI: 10.1007/s11657-022-01171-0
|View full text |Cite
|
Sign up to set email alerts
|

The interdisciplinary fracture liaison service improves health-related outcomes and survival of older adults after hip fracture surgical repair

Abstract: Summary Due to the high burden of fragility fractures, we developed an interdisciplinary FLS care pathway for early management and monitoring of older adults discharged from a high-volume trauma center after hip fracture repair. Interdisciplinary FLS effectively improves up to 1-year adherence to treatments for secondary prevention of fragility fractures, reduces health facility admission, and improves long-term survival. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(42 reference statements)
0
8
0
Order By: Relevance
“… 55 An absence of prior antiosteoporosis treatment was, however, observed to be associated with increased postfracture mortality, 12 and a clinical pathway focusing on improving post-fracture treatment rates, known as fracture liaison service, has also been shown to reduce mortality. 56 , 57 However, fracture liaison service is typically implemented at institutions by self-selected hospital champions using finite external funding, because it is currently not a standard practice to assess and treat postfracture patients by the time they are discharged from fracture care. Current postfracture assessment and treatment rates thus remain alarmingly low.…”
Section: Discussionmentioning
confidence: 99%
“… 55 An absence of prior antiosteoporosis treatment was, however, observed to be associated with increased postfracture mortality, 12 and a clinical pathway focusing on improving post-fracture treatment rates, known as fracture liaison service, has also been shown to reduce mortality. 56 , 57 However, fracture liaison service is typically implemented at institutions by self-selected hospital champions using finite external funding, because it is currently not a standard practice to assess and treat postfracture patients by the time they are discharged from fracture care. Current postfracture assessment and treatment rates thus remain alarmingly low.…”
Section: Discussionmentioning
confidence: 99%
“…These programs, because of their smaller size, have the theoretical advantage of enhanced “grass roots” coordination; however, the absence of national coordinated oversite can challenge program cohesion. An article from Italy compared a cohort of hip fracture patients who entered the FLS care pathway with those managed according to the usual traumatologist model of care 12 . The FLS care pathway was a structured multidisciplinary program involving follow-up telephone calls, dietary counseling, fall and fracture prevention training, and pharmacologic counseling—engaging and coordinating nurses, dieticians, physical therapists, and pharmacologists.…”
Section: Organization and Structure Of Multidisciplinary Pfcpmentioning
confidence: 99%
“…A study comparing pre-FLS and post-FLS care at a single center in Spain showed antiosteoporotic drugs were more frequently prescribed (78% after and 12% before), adherence to treatment at 1 year increased (39% after and 3% before), and 1-year mortality was reduced (hazard ratio [HR] 0.75, 95% CI 0.59-0.96) 27 . Another article compared the adherence with secondary fragility fracture prevention methods between a cohort of hip fracture patients who entered the FLS care pathway (FLS-CP) with those managed according to the usual traumatologist model of care in a community in Italy 12 . FLS-CP patients had a higher initiation rate and 1-year adherence rate to all measures (vitamin D and Ca 87.7% vs. 36.9%, antiosteoporosis drugs 75% vs. 8%, and fracture prevention therapy 72% vs. 6%).…”
Section: Effectiveness and Outcomes Of Multidisciplinary Pfcpmentioning
confidence: 99%
“… 11 , 12 To reduce the incidence of a second FF, several prevention programs have been proposed, and good outcomes were reported in terms of both mortality and treatment adherence. 12 32 The fracture liaison service (FLS) is one of the proposed models to effectively manage a patient with an FF. Generally, FLS refers to a multidisciplinary functional coordination structure established in a third-level hospital.…”
Section: Introductionmentioning
confidence: 99%
“… 32 , 34 This kind of approach has been proven to be cost-effective, with an average reduction of 20% in the treatment gap, a 20% increase in adherence to anti-fracture treatment, and a 5% reduction in the rate of re-fracture and mortality. 12 32 Adherence to anti-fracture treatment is one of the pivotal points in the prevention of FFs. 35 …”
Section: Introductionmentioning
confidence: 99%